2014
DOI: 10.1038/cdd.2014.148
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of white adipocyte progenitors induces beige adipocyte differentiation and suppresses obesity development

Abstract: Overgrowth of white adipose tissue (WAT) in obesity occurs as a result of adipocyte hypertrophy and hyperplasia. Expansion and renewal of adipocytes relies on proliferation and differentiation of white adipocyte progenitors (WAP); however, the requirement of WAP for obesity development has not been proven. Here, we investigate whether depletion of WAP can be used to prevent WAT expansion. We test this approach by using a hunter-killer peptide designed to induce apoptosis selectively in WAP. We show that target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 62 publications
7
80
2
Order By: Relevance
“…Interestingly, beige fat displays a smooth muscle-like signature of gene expression profiles (190), suggesting a potential lineage relationship between beige adipocytes and smooth muscle cells. Diverse beige progenitor lineages may exist; in mice, both beige adipocyte-specific progenitors and beige/white adipocyte-bipotent PDGFRα + progenitors have been reported (60, 178, 338). Notably, a subpopulation of PDGFRα + mesenchymal progenitors (PDGFRα + CD9 high ) also differentiates into fibrogenic cells in obesity, promoting adipose tissue fibrosis (201).…”
Section: Bat and Beige Fat Developmentmentioning
confidence: 99%
“…Interestingly, beige fat displays a smooth muscle-like signature of gene expression profiles (190), suggesting a potential lineage relationship between beige adipocytes and smooth muscle cells. Diverse beige progenitor lineages may exist; in mice, both beige adipocyte-specific progenitors and beige/white adipocyte-bipotent PDGFRα + progenitors have been reported (60, 178, 338). Notably, a subpopulation of PDGFRα + mesenchymal progenitors (PDGFRα + CD9 high ) also differentiates into fibrogenic cells in obesity, promoting adipose tissue fibrosis (201).…”
Section: Bat and Beige Fat Developmentmentioning
confidence: 99%
“…Daquinag et al [40] have shown that targeted WAP cytoablation results in a long-term WAT growth suppression, despite increased caloric intake in a mouse model of dietary-induced obesity. They also showed that WAP depletion results in a compensatory population of beige adipocytes.…”
Section: Potential Effect Of Intervention Upon Wap Cells On Obesity Dmentioning
confidence: 99%
“…Consistent with the reported thermogenic capacity of the later tissue, WAP-depleted mice display increased energy expenditure. Thus, targeting white adipocyte progenitors could render an effective strategy to sustained modulation of WAT metabolic activity [40] .…”
Section: Potential Effect Of Intervention Upon Wap Cells On Obesity Dmentioning
confidence: 99%
“…EO771 cells were then grafted into the mammary fat pad and tumors were allowed to form. Formalin-fixed paraffin-embedded tissues were sectioned and analyzed by immunofluorescence as described 49,50 using anti-IL-22 bs-2623R (Bioss, 1:100) and anti-IL-22R bs-2624R (Bioss, 1:200) antibodies, followed by secondary Alexa 488-conjugated and Cy3-conjugated antibodies. Nuclei were visualized with DAPI staining.…”
Section: Systemic Circulation Of Il-22 Is Increased In Obesitymentioning
confidence: 99%
“…Experimental compounds targeting adipose stroma prevented diet-induced obesity and tumor growth in mouse models. 44,49 Future studies will establish if this approach can complement approved anti-obesity and anti-cancer treatments. …”
Section: Infiltration Of Wat By Il-22-expressing Leukocytes and Il-22mentioning
confidence: 99%